Remote Patient Management May Reduce All-Cause Mortality in Patients With Heart-Failure and Renal Impairment - Naik, Marcel G.; Budde, Klemens; Koehler, Kerstin; Vettorazzi, Eik; Pigorsch, Mareen; Arkossy, Otto; Stuard, Stefano; Duettmann, Wiebke; Koehler, Friedrich; Winkler, Sebastian (Frontiers in Medicine, 2022)
Background Remote patient management (RPM) in heart failure (HF) patients has been investigated in several prospective randomized trials. The Telemedical Interventional Management in Heart Failure II (TIM-HF2)-trial showed reduced all-cause mortality and hospitalizations in heart failure (HF) patients using remote patient management (RPM) vs. usual care (UC). We report the trial's results for prespecified eGFR-subgroups. Methods TIM-HF2 was a prospective, randomized, controlled, parallel-group, unmasked (with randomization concealment), multicenter trial. A total of 1,538 patients with stable HF were enrolled in Germany from 2013 to 2017 and randomized to RPM (+UC) or UC. Using CKD-EPI-formula at baseline, prespecified subgroups were defined. In RPM, patients transmitted their vital parameters daily. The telemedical center reviewed and co-operated with the patient's General Practitioner (GP) and cardiologist. In UC, patients were treated by their GPs or cardiologist applying the current guidelines for HF management and treatment. The primary endpoint was the percentage of days lost due to unplanned cardiovascular hospitalizations or death, secondary outcomes included hospitalizations, all-cause, and cardiovascular mortality. Results Our sub analysis showed no difference between RPM and UC in both eGFR-subgroups for the primary endpoint (<60 ml/min/1.73 m2: 40.9% vs. 43.6%, p = 0.1, ≥60 ml/min/1.73 m2 26.5 vs. 29.3%, p = 0.36). In patients with eGFR < 60 ml/min/1.73 m2, 1-year-survival was higher in RPM than UC (89.4 vs. 84.6%, p = 0.02) with an incident rate ratio (IRR) 0.67 (p = 0.03). In the recurrent event analysis, HF hospitalizations and all-cause death were lower in RPM than UC in both eGFR-subgroups (<60 ml/min/1.73 m2: IRR 0.70, p = 0.02; ≥60 ml/min/1.73 m2: IRR 0.64, p = 0.04). In a cox regression analysis, age, NT-pro BNP, eGFR, and BMI were associated with all-cause mortality. Conclusion RPM may reduce all-cause mortality and HF hospitalizations in patients with HF and eGFR < 60 ml/min/1.73 m2. HF hospitalizations and all-cause death were lower in RPM in both eGFR-subgroups in the recurrent event analysis. Further studies are needed to investigate and confirm this finding.